Simulating Radio Coverage with Polar Coordinates for Wireless Networks - Adasme-Soto, P; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper presents a simulation study of polar coverage signaling which can be applied to different current wireless communication systems. In particular, we use the Polar Radio Coverage feature of Radio Mobile software version 11.6.6 in order to perform an empirical study in real geographical areas including Las Condes and Valparaiso which are two locations in Chile. In this predictive study, all parameters are configured for both the radio base stations (RBS) and mobile stations (MS) located in certain points of the proposed coverage area. This allows obtaining the signal strength and visualizing the range in the covered maps. Subsequently, the data is exported to Google Earth Pro in order to identify the areas without coverage where it is not possible to establish of a point-to-point link communication. Consequently, the establishment of coverage in a given area will guarantee certain signal levels in the receiving equipment while considering different values for the coverage radius and azimuth. Finally, the proposed approach can be applied in all wireless communications systems allowing additionally Path Loss and E-field strength analysis. © 2021 IEEE.